Fabrication and characterization of thin 142, 150Nd targets for the study of dynamics of heavy-ion induced reactions. (April 2021) - Biswas, Saumyajit; Abhilash, S.R.; Kabiraj, D.; Biswas, Rohan; Umapathy, G.R.; Ojha, S.; Chakraborty, A.
Abstract: The fabrication of targets from rare earth elements are extremely difficult due to their highly active reacting properties. Hence, the fabrication, transfer, and storage of these types of targets using in-vacuum transfer facilities is found to be the ideal solution. However, the required instrument for this purpose is very expensive and not easy to maintain for a long period of time. Search for an alternate simplified method and its effective usage for fabrication and preservation of rare earth targets is the need of the hour. The present manuscript describes such a method which has been successfully used in the case of fabricating thin targets from the enriched Neodymium (Nd) isotopes. Since the target materials of enriched Nd-isotopes are expensive, devising a procedure which can produce a maximum number of targets with the use of minimum amount of material is very important. Isotopically enriched thin, uniform and durable Neodymium ( 142, 150 Nd) targets of ∼ 150 μ g /cm 2 thickness have been fabricated by using electron beam bombardment technique within a diffusion pump based High Vacuum (HV) coating unit. The targets have been fabricated at the target laboratory of the Inter University Accelerator Centre (IUAC), New Delhi. The sandwiched targets have been prepared with a carbon backing layer of thickness ∼ 25 μ g /cm 2 and a carbon capping layer of thickness ∼ 10 μ g /cm 2 . The present article brings out different aspects such as: (i) the detailed fabrication procedure along with the various challenges faced (heat damage, peeling off, oxidizing nature of the target etc. ) has been reported in this article; (ii) the measurements involving Energy Dispersive X-ray Spectroscopy (EDS), and Rutherford Backscattering Spectrometry (RBS) have been carried out to assess the purity, uniformity, and elemental composition of the targets. The analysis of the acquired data from the measurements suggests that the prepared targets are found to be free from any high-Z contaminating elements. These targets have successfully been used in heavy-ion induced nuclear physics experiments using the General Purpose Scattering Chamber (GPSC) available at IUAC, New Delhi. Highlights: Thin targets are very much needed for fruitful study of heavy-ion reaction dynamics. High Vacuum evaporation chamber has been used for target fabrication. Sandwiched targets were fabricated using thin capping and backing layers of carbon. The prepared targets have been characterized through EDS and RBS measurements. The prepared thin 142, 150 Nd targets have successfully been used in the heavy-ion reaction studies.